A internet como meio para gerar valor à marca - Fonseca, Aldair Almeida (2011)
In regards to the importance of branding and the value of management to contemporary organizations and the relevance of the Internet on the world stage, this study aims to understand how the Internet can be used as a mean to generate value to the brand in addition to understanding how Social Media (social networking, virtual communities, blogs and forums), sites other than Google Adwords, Adsense and Analytics can be useful in creating value for brands and how these features can influence the perception of value by consumers. This study was developed through qualitative research. The bibliographic review on the brand value was based on the concepts of Aaker (1998, 2007) and Keller (2006), as these authors support the line taken in this project that the brand value lies in its positioning in the minds of consumers , as is, the quota that the brand occupies in the consumers' mind , on the issue Internet, we used bibliographic concepts present in Castells (1999, 2001) as well as articles and specialized sites that deal with the issue. The field research was developed through case study, and to ensure the reliability of the survey, we used the case study protocol based on the model proposed by Yin (2001). To answer questions presented a research was made on a study of a single case in a company specializing in the development and improvement of online marketing, where a survey was conducted through exploratory approach of open questions in order to investigate how this company through the means of Internet adds value to your brand, and thus present results that demonstrate the relevance of the Internet as a creator of value. The main conclusions of this study indicate that the Internet and its resources are a key resource for the generation of value for contemporary companies in the current scenario, the increased importance of the Internet shows that companies need to understand and leverage the resources available on it to obtain consistent results and perennials